Kondycja podmiotu wobec upadku Rzeczypospolitej. Treny Józefa Morelowskiego - Bąkowska, Patrycja (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The main aim of the article is a reading of Józef Morelowski’s Laments as a text which expresses the crisis of the subject. The author of the article proposes a an interpretation of this cycle of poems, written after the Third Partition of Poland, in the context of the antique and Old Polish tradition. It gives an opportunity to show and to emphasize diverse ways of self-manifestation in the poetical works. It appears that using literary topoi and stylistic devices rooted in culture is an attempt to overcome the crisis of the subject. Furthermore, taking into consideration the role of tradition and literary convention might help us to reconsider the state of research and to rethink conclusions, which have been reached so far, about the so-called romantic breakthrough.